Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41467-021-27854-9
|View full text |Cite
|
Sign up to set email alerts
|

Towards a generic prototyping approach for therapeutically-relevant peptides and proteins in a cell-free translation system

Abstract: Advances in peptide and protein therapeutics increased the need for rapid and cost-effective polypeptide prototyping. While in vitro translation systems are well suited for fast and multiplexed polypeptide prototyping, they suffer from misfolding, aggregation and disulfide-bond scrambling of the translated products. Here we propose that efficient folding of in vitro produced disulfide-rich peptides and proteins can be achieved if performed in an aggregation-free and thermodynamically controlled folding environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The cell-free CHO system was capable of producing the selected model Nbs in yields up to ∼12 μg/ml ( Figure 2 ) which was sufficient for a straight-forward functional analysis of Nbs by ELISA, directly following cell-free synthesis and without requiring a purification step. In comparison, scFv and Fab fragments have been produced in yields of 50–200 μg/ml in a cell-free E. coli system ( Wu et al, 2022 ). Unlike E. coli , the cell-free reticulocyte system is related to rather low protein yields ( Carlson et al, 2012 ; Gregorio et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cell-free CHO system was capable of producing the selected model Nbs in yields up to ∼12 μg/ml ( Figure 2 ) which was sufficient for a straight-forward functional analysis of Nbs by ELISA, directly following cell-free synthesis and without requiring a purification step. In comparison, scFv and Fab fragments have been produced in yields of 50–200 μg/ml in a cell-free E. coli system ( Wu et al, 2022 ). Unlike E. coli , the cell-free reticulocyte system is related to rather low protein yields ( Carlson et al, 2012 ; Gregorio et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most recent application of cell-free systems for venom toxin production involved the modification of a thermodynamically controlled E. coli -based cell-free system (AC-assisted Ec CFS) to produce a variety of complex, bioactive folded peptides from a range of sources. These included the spider toxins DC1a ( Diguetia canities ) and Pn3a ( Pamphobeteus nigricolor ) as well as the tick toxin HT-1 ( Ixodes holocyclus ) ( Wu et al, 2022 ). All these toxins are heavily cysteine-crosslinked, showing that cell-free systems can produce challenging venom components ( Wu et al, 2022 ).…”
Section: How Synthetic Biology Enables Access To Venom Gene Productsmentioning
confidence: 99%
“…These included the spider toxins DC1a ( Diguetia canities ) and Pn3a ( Pamphobeteus nigricolor ) as well as the tick toxin HT-1 ( Ixodes holocyclus ) ( Wu et al, 2022 ). All these toxins are heavily cysteine-crosslinked, showing that cell-free systems can produce challenging venom components ( Wu et al, 2022 ).…”
Section: How Synthetic Biology Enables Access To Venom Gene Productsmentioning
confidence: 99%
“…Benchmarking of LTE against several leading cell-free systems demonstrated that it is capable of producing large human proteins in full-length and monodispersed form on par with mammalian cell-free systems . In our recent study, we showed the significant potential of LTE to produce folded proteins owing to co-translational chaperon assistance inherent to eukaryotic systems in contrast to the bacterial system …”
Section: Introductionmentioning
confidence: 98%
“…21 In our recent study, we showed the significant potential of LTE to produce folded proteins owing to cotranslational chaperon assistance inherent to eukaryotic systems in contrast to the bacterial system. 22 We subsequently expanded the platform by coupling it to high-throughput protein−protein interaction analysis known as the amplified luminescent proximity homogeneous assay screen (AlphaLISA). 23 It is a proximity bead-based assay in which a luminescent signal is generated when the acceptor and donor beads come into proximity as a result of the interaction of molecules attached to their surface.…”
Section: ■ Introductionmentioning
confidence: 99%